Sex workers' behavior in a district of Cebu City, Philippines and its implication to AIDS prevention - Sansarit, Jose Rene M. (Danyag :the UPV journal of humanities and social sciences, 2009)
"As a high risk group, sex workers are often the convenient subjects for researchers and policies aimed at modifying behavior against AIDS. Sexual behavior, however, as maintained in this paper is intimately linked to other social realities, expectations, and valuation of one's identity. An ethnographic description of sex work in a district of Cebu City shows how this behavior is played along the interacting roles and statuses and is being negotiated in such locality. Knowledge about the life of sex workers in effect can fully sensitize AIDS prevention strategies to include community members who integrally take part in the discourse of sex work."